Bioprocessing of seaweed into protein enriched feedstock: process optimization and validation in reactor - Jamal, Parveen; Saheed, Olorunnisola Kola; Jaswir, Irwandi; Tijani, Ruqayyah I. D.; Ansari, Abdul Haseeb (Faculty of Food Science & Technology, University Putra Malaysia, 2017)
Solid state bioconversion (SSB) of Ulva seaweed for protein enrichment was conducted over 7-days using Phanerochaete chrysosporium (P. chrysosporium). One-factor-at-a-time (OFAT) optimization of process parameters revealed 70% for moisture content, 9% for inoculum size and 7% for minerals. Optimum substrate depth in 1 kg reactor was 12 mm and the protein increased from 88.51 mg/g to 107.89 mg/g. Fourier transformation infrared spectroscopy (FTIR) analysis showed modifications in the polysaccharide resulting from SSB. Soluble and reducing sugars concentrations improved by 168.88% (from 33.74±0.51 mg/g to 90.72±1.38 mg/g) and 198.95% (from 0.13±0.05 mg/g to 0.40±0.01 mg/g), while total carbohydrate reduced to 107.15±1.21 mg/g from initial concentration of 109.39±1.33 mg/g